Germination and acclimatization of Melocactus sergipensis Taylor & Meiado - Bravo Filho, Eronides Soares; de Santana, Marlucia Cruz; Santos, Paulo Augusto Almeida; Ribeiro, Adauto de Souza (Iheringia, Série Botânica., 2019)
Melocactus sergipensis is endemic to the state of Sergipe in northeastern Brazil, with an estimated population of 100 adult individuals. The present study evaluated the effect of imbibition on the in vitro and ex vitro germination of M. sergipensis seeds, and the influence of different substrates on acclimatization. The experimental design was completely randomized, and the data were evaluated using an Analysis of Variance with Tukey’s test, considering a 5% significance level. Soaking the seeds for 6 h in 2 mg L-1 GA3 increased in vitro germination significantly, from 10% to 38%, although no significant variation was found in germination rates among the different substrates. Acclimatization occurred in all substrates, with a survival rate of over 88%.